2001
DOI: 10.1159/000055739
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Distant Metastases in Head and Neck Cancer

Abstract: The detection and treatment of metastatic cancer continues to be a challenge for the head and neck oncologist. Unfortunately, head and neck cancer patients who develop distant metastases commonly present late in their course and rapidly succumb to their disease, despite advances in imaging technologies and increased sophistication of biochemical analyses. The development of a rational approach to detection and treatment of metastatic head and neck cancers should begin with an understanding of how these tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 91 publications
1
14
0
1
Order By: Relevance
“…In previous reports, clinically palpable nodes, histologic evidence of metastatic lymph node disease, the number of positive lymph nodes involved, and extracapsular spread have been related to the risk of developing distant metastases 12, 14, 16, 21, 24, 29. As did other authors,21, 24, 30, 31 we also found lymph node status and extracapsular lymph node extension14, 32–34 to have a prognostic value for the development of distant metastases. It may be that tumors with cervical lymph node metastases are more aggressive; alternatively, it may be just that tumors with distant metastases were diagnosed later, allowing progression.…”
Section: Discussionsupporting
confidence: 88%
“…In previous reports, clinically palpable nodes, histologic evidence of metastatic lymph node disease, the number of positive lymph nodes involved, and extracapsular spread have been related to the risk of developing distant metastases 12, 14, 16, 21, 24, 29. As did other authors,21, 24, 30, 31 we also found lymph node status and extracapsular lymph node extension14, 32–34 to have a prognostic value for the development of distant metastases. It may be that tumors with cervical lymph node metastases are more aggressive; alternatively, it may be just that tumors with distant metastases were diagnosed later, allowing progression.…”
Section: Discussionsupporting
confidence: 88%
“…Several clinical and histological characteristics, such as cellular differentiation, pattern of tumour invasion, inflammatory response, perineural infiltration, lymphatic and/or vascular invasion, cartilage and/ or bone infiltration, lymph node metastasis, capsular rupture, and positive surgical margins have been considered to be predictors of distant metastasis in head and neck cancers 10 . In this study, the significant predictors of distant metastasis were clinical stage, positive lymph nodes, facial paralysis, and invasion of adjacent structures.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent failures affecting the prognosis involve distant metastases 10 . Data from the literature show that distant metastasis rates in patients with carcinomas of parotid, submandibular, and minor salivary glands are higher than 17%, 37% and 24%, respectively 2,15,20,22,23 .…”
mentioning
confidence: 99%
“…SCCs progress from their primary site as a result of enzyme elaboration (matrix metalloproteinases) which destroys the basement membrane and the laminin components of the subdermal extracellular matrix and reaches the stroma lymphatic network. The next step is invasion of the lymphatic channels, where the tumoral cells plus lymphocytes and platelets form a metastatic embolus, which flows sequentially through the regional lymphatic basin from levels I to IV, gaining access to the vascular system [11]. The initial lymph node metastatic invasion has been classified by Hermanek et al [12] into three types: (i) the presence of isolated or small clusters of tumor cells within the lymph node sinuses without implantation; (ii) infiltration of lymph node parenchyma by cancer cells B/2 mm in diameter (micrometastases); and (iii) infiltration of lymph nodes by tumors /2 mm in diameter (metastases).…”
Section: Discussionmentioning
confidence: 99%